CHARACTERISTICS OF PATIENTS HOSPITALIZED WITH 2009 H1N1 INFLUENZA IN A TERTIARY CARE HOSPITAL IN SOUTHERN SAUDI ARABIA - Adnan Agha; Abdul Qader Alrawi; Abdelhaleem Bella; Mohammed S. AlAyed (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Background Pandemic influenza A (H1N1) virus emerged and spread globally in the spring of 2009. We describe the clinical features of the patients who were hospitalized with 2009 H1N1 influenza July 2009 to June 2010 in a tertiary care hospital in Khamis Mushyt, Saudi Arabia. We analyzed the clinical and laboratory variables in order to determine predictors of poor outcome Methods We performed a prospective study in all patients who were hospitalized for at least 48 hours and with a positive test for 2009 H1N1 virus through RT-PCR(real time polymerase chain reaction). Their epidemiological, clinical, biochemical characteristics were collected and the hospital course of the patients with eventual outcome (discharge or death) was observed. We applied a logistic regression analysis to determine the best predictor of death.